ბერძნული და რომაული ცივილიზაციები: ურთიერთქმედება და ინოვაცია - მანძილასი დიმიტრიოს (ლოგოსი, 2021)
To the Romans, the Greek civilization was a source of inspiration in every level (architecture, art, ideas, literature, mythology, religion). Τhe influence of the Greek culture on the Romans who studied in depth and assimilated the Greek education (especially in the Roman period and because of it), and the process known as syncretism, created the Greco-Roman civilization, which in turn influenced and continues to influence catalytically the Western civilization. Moreover, Roman imitation (imitatio) and emulation (aemulatio) of Greek liter- ature created Latin literature through which the Humanists got to know and preserve the ancient Greek texts and thus the thought and mentality of the Greeks. Both literatures continue to be studied all over the world because of their massive, globally radiating, effect. Furthermore, Greek loans on Latin lan- guage became a common phenomenon that spread later on many languages, a large part of which contains vocabulary of Greek origin. Following the opposite direction, words, phrases and expressions entered Modern Greek either un- changed from Latin either via re-borrowing, either moderated through the Ro- mance Languages, enriching the linguistic wealth of it in different language environments.